Image Recognition Using a Neural Network (Using Convolutional Neural Networks) - Zena Fouad Rasheed; Raghdah A. Abdulrazzq; Mohammed Taher A. Mohammed; Sara Sadeq (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2026)
An essential decision in constructing a neural network for any application is determining the appropriate representation of the data for presentation. Advancements in training techniques, such as changes to data augmentations and optimization methods, have greatly contributed to the notable progress made in the field of image classification research. Identifying and categorizing animals presents a substantial obstacle for researchers. The classification of animals consists of five main categories: mammals, amphibians, reptiles, fowls, and fish, each including a wide range of species. Therefore, we present an innovative method for recognizing and assessing classifications of vertebrate organisms by the use of deep Convolutional Neural Networks (CNN). The main objective of this article is to improve an intelligent model based on CNNs for the precise classification of vertebrate animals using image data. Basically, the goal is to create an efficient system that can be applied in real-world scenarios, including environmental monitoring, automated biological research, and educational applications. This research focuses on developing an efficient approach for classifying vertebrate animals using a deep CNN. CNNs, inspired by the human brain’s structure, are powerful deep learning models eligible of processing large image datasets to achieve high precision in recognition tasks. The study utilizes CNN architectures trained on the Kaggle dataset to evaluate their performance in animal image classification. Through the application of real-time data augmentation and dropout techniques, the proposed models demonstrated exceptional precision, achieving an accuracy rate of 99.6%.